Physicochemical properties, eating and cooking quality and genetic variability: a comparative analysis in selected rice varieties of South India - Febina M; Deepa John; Maya Raman (Food Production, Processing and Nutrition, 2023)
Abstract The physicochemical characteristics and digestibility properties of rice are greatly influenced by its genetic variability. In this study, we attempt to understand the overall quality of five traditional and popularly consumed rice varieties of Kerala. The major traits affecting the eating and cooking quality of rice such as amylose content (AC), gel consistency (GC) and gelatinization temperature (GT) were determined and correlated with the expression of the starch-synthesis-related genes (SSRGs). The Wx is a major SSRG, which modulates the amylose content and the eating as well as cooking qualities of rice. The rice varieties including, Jaya, Matta and Rakthashali were found to have intermediate amylose content (Wx a allele) while Kuruva and Pokkali were found to have high Amylose Content (Wx a allele). The glycemic index (GI) of all varieties was found to be in the range of 51.0–58.6. Among the screened rice varieties, Pokkali was found to have the lowest glycemic index and digestibility with appreciable eating and cooking qualities. Pokkali rice, with its low GI (51.0), could be a recommended variety for diabetes management. Furthermore, the rice eating and cooking qualities, and plant breeding techniques coordinated by the expression of the starch synthesis-related gene (Wx), could be a novel approach to improve the valuable germplasm. Graphical Abstract